2019
DOI: 10.1136/rmdopen-2019-001067
|View full text |Cite
|
Sign up to set email alerts
|

Transition phase towards psoriatic arthritis: clinical and ultrasonographic characterisation of psoriatic arthralgia

Abstract: ObjectiveNon-specific musculoskeletal pain is common in subjects destined to develop psoriatic arthritis (PsA). We evaluated psoriatic patients with arthralgia (PsOAr) compared with psoriasis alone (PsO) and healthy controls (HCs) using ultrasonography (US) to investigate the anatomical basis for joint symptoms in PsOAr and the link between these imaging findings and subsequent PsA transition.MethodsA cross-sectional prevalence analysis of clinical and US abnormalities (including inflammatory and structural le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 31 publications
1
86
0
Order By: Relevance
“…Moreover, arthralgia mainly in female PsO patients is a strong predictor for PsA development ( 9 ). This finding was confirmed by Zabotti et al ( 10 ) in 2019 in a longitudinal study.…”
Section: The Transition From Psoriasis To Psoriatic Arthritissupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, arthralgia mainly in female PsO patients is a strong predictor for PsA development ( 9 ). This finding was confirmed by Zabotti et al ( 10 ) in 2019 in a longitudinal study.…”
Section: The Transition From Psoriasis To Psoriatic Arthritissupporting
confidence: 77%
“…A recent study showed that, in this phase, tenosynovitis was the most significant contributor to the reported musculoskeletal symptoms (PsO vs. PsO with arthralgia vs. PsA). In the US, in a high proportion of patients, tenosynovitis especially of the flexor tendon of the hands was detected (in 29.5% of the arthralgia patients compared to 5.3% in the PsO group) ( 10 ), whereas active enthesitis and synovitis did not reach a significant difference. In the longitudinal part of the study, in the US, determined enthesitis was the only US feature linked to the future evolution of PsA.…”
Section: Imaging Techniques For the Detection Of Early Changes In Angmentioning
confidence: 98%
“…Two initial asymptomatic phases, at first with aberrant activation of the immune system which may originate from the skin, intestinal mucosa, or the entheses and then with subclinical signs of musculoskeletal inflammation or with soluble biomarkers (e.g., ESR, CRP). Lastly, a prodromal symptomatic transition phase may exist characterized by nonspecific musculoskeletal pain, recently defined as psoriatic arthralgia, and fatigue [ 8 , 20 ]. This prodromal phase can be difficult to identify due to non-specific symptoms and possible PsA disease mimics, such as incipient or concomitant osteoarthritis, fibromyalgia, or chronic pain related to psoriatic comorbidities [ 21 , 22 , 23 ].…”
Section: From Pso To Psa In the Dermatology-rheumatology Combined mentioning
confidence: 99%
“…This prodromal phase can be difficult to identify due to non-specific symptoms and possible PsA disease mimics, such as incipient or concomitant osteoarthritis, fibromyalgia, or chronic pain related to psoriatic comorbidities [ 21 , 22 , 23 ]. There are preliminary evidences that sonographic determined enthesitis might be associated with subsequent clinical disease evolution [ 20 , 24 , 25 ], but these results are preliminary and require further validation. However, as discussed below, there is a tremendous need to study PsO phenotypes themselves more closely and to use imaging in the context of psoriasis patterns to better define the pre-clincal phases of PsA.…”
Section: From Pso To Psa In the Dermatology-rheumatology Combined mentioning
confidence: 99%
“…Delays in the route to PsA diagnosis can commonly occur over several months [ 4 ], which can lead to mental distress and patient dissatisfaction (see Figure 1 ). Symptoms related to arthralgia (pain, stiffness, tenderness) or evidence of subclinical synovitis may confer a higher risk for developing PsA [ 5 , 6 , 7 ]. The socioeconomic burden of disease is also substantial with high healthcare costs and comorbidity, reduced work ability, and lower pay that may be present months prior to diagnosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%